Outcomes and prognostic factors of neuroendocrine cervical cancer in the National Cancer Institute of Thailand: A retrospective cohort study - Siripaopradit, Suwaree; Pitakkarnkul, Supakorn Pitakkarnkul; Ratanasrithong, Panwad; Foongfaung, Sujira (Asian Pacific Journal of Cancer Care, 2020)
Background: Neuroendocrine carcinoma of the cervix (NECC) is a rare tumor with an aggressive natural course. Objective: This study was to investigate the outcomes and prognostic factors for NECC patients who had been treated at the National Cancer Institute of Thailand (NCI). Methods: NECC patients who had been treated between January 2008 to December 2017 at NCI of Thailand were review. Data were collected from medical records, tumor registry files, and civil registration system. The impacts of clinical and pathologic risk factors on the overall survival (OS) and progression-free survival (PFS) were evaluated using Kaplan–Meier survival analyses and the prognostic factor was determined by univariate Cox regression analysis. Result: Thirty-three NECC patients including 12 patients early-stage patients (FIGO stage I-IIA) and 21 patients advanced stage patients (FIGO stage IIB-IVA) were reviewed. All of the patients in the early stage underwent radical hysterectomy and lymph node dissection (RHND) with or without neoadjuvant chemotherapy. Ten patients received adjuvant therapy with pelvic radiation and/or cisplatin-etoposide following operation. Median OS and PFS among early-stage patients were 25.69 months and 18.65 months, respectively. Treatments among patients with advanced-stage included initial chemotherapy, initial concurrent chemoradiation (CCRT), and only CCRT. Patients receiving initial chemotherapy had better PFS (81.4 months) and OS (81.4 months) compared to those who received initial CCRT (PFS 9.0 months; OS 13.2 months; P=0.013) or only CCRT (PFS 13.0 months; OS 16.1months; P=0.016). No statistically significant factors associated with survival were noted. Conclusion: Patients with NECC carried a poor prognosis even in the early stage of the disease. Systemic chemotherapy may be required for all stages of this highly aggressive cancer.